Prevalence and Risk Factors of Depression and Anxiety in Essential Tremor Patients: A Cross-Sectional Study in Southwest China - Huang, Hongyan; Yang, Xinglong; Zhao, Quanzhen; Chen, Yalan; Ning, Pingping; Shen, Qiuyan; Wang, Hui; An, Ran; Xu, Yanming (Frontiers in Neurology, 2019)
Background: Essential tremor (ET) is one of the most common movement disorders, and it has been associated with anxiety and depression, but risk factors for these mental disorders are unclear. This study aimed to evaluate the prevalence and potential risk factors of depression and anxiety in ET patients in China. Methods: This cross-sectional study involved 245 Han Chinese patients with ET. Depression was assessed using the Hamilton Depression Rating Scale-24 Items, and anxiety was assessed using the Hamilton Anxiety Rating Scale. Clinico-demographic characteristics were compared between patients with or without depression or anxiety. Results: We revealed that 63.3% of patients had at least mild anxiety and 54.3% at least mild depression. Severity of anxiety or depression was correlated with lower Mini-Mental State Exam score (P=0.028 and P=0.002 respectively), higher self-report functional disability score (P=0.027 and P=0.003 respectively), as well as the presence of tremor in the neck (both P < 0.001), face (P=0.025 and P < 0.001 respectively), or voice (both P < 0.001). Binary logistic regression identified female sex, presence with cranial tremor and greater functional disability score as risk factors of anxiety; the last two factors were also the determinants of depression. Neither anxiety nor depression correlated with physician-assessed severity of arm or leg tremor. Conclusion: Chinese ET patients show high prevalence of depression and anxiety. ET patients should be screened for these mental disorders, especially women and those with cranial tremor and self-reported functional disability.